ANALISIS PENGARUH MEREK, PROMOSI, HARGA, DAN E-SERVICE QUALITY TERHADAP KEPUASAN PELANGGAN DALAM PENGGUNAAN E-COMMERCE SHOPEE (Studi Kasus di Masyarakat Kabupaten Wonogiri) - MAHFUD - KUNCORO; SRI ISFANTIN PUJI LESTARI; AGUS ISFANTIN TRIATMONO (JURNAL WIRANOMIKA, 2024)
Abstract : This study aims to determine the variables of Brand (X1), Promotion (X2), Price (X3) and E-Service Quality (X4) that affect Customer Satisfaction in the Use of Shopee E-Commerce (Y) in the Wonogiri Regency Community. This study used multiple linear regression which was analyzed using IBM SPSS 25 software, The results of the regression equation obtained were Y = 1.195 + 0.033 X1 + 0.038 X2 + 0.366 X3 + 0.435 X4 + e. The data used is primary data using the entire a population of one hundred respondents was studied in the Wonogiri Regency Community. The findings showed that the Brand variable (X1) tcount (0.240) < ttable (1.985), the hypothesis was rejected, which means there is no partially significant effect on Customer Satisfaction (Y) in the use of Shopee e-commerce. Promotion (X2) tcount (0.695) < t table (1.985), hypothesis rejected, which means there is no partially significant effect on Customer Satisfaction (Y) in the use of Shopee e-commerce. Price (X3) tcalculate (4,318) > ttable (1,985), hypothesis accepted, which means that there is a partially significant effect on Customer Satisfaction (Y) in the use of Shopee e-commerce. E-Service Quality (X4) tcount (4.964) > ttable (1.985), hypothesis accepted, which means that there is a partially significant effect on Customer Satisfaction (Y) in the use of Shopee e-commerce in Wonogiri Regency Community. The results of Test F were obtained Fcalculate (57.571) > Ftable (2.47), the hypothesis was rejected, which means that there is a simultaneous significant influence of the variables Brand (X1), Promotion (X2), Price (X3) and E-Service Quality (X4) on Customer Satisfaction (Y). Of the four independent variables, the dominant is E-Service Quality (X4) where the calculated value is (4.964) > ttable (1.985), which means that the hypothesis is proven correct.Â Keywords: Brand (X1), Promotion (X2), Price (X3) and E-Service Quality (X4) and Customer Satisfaction (Y)